Biophysical and biochemical studies of a major endoglucanase secreted by Xanthomonas campestris pv. campestris. - Rosseto, Flavio Rodolfo; Manzine, Livia Regina; Neto, Mario de Oliveira [UNESP]; Polikarpov, Igor (Elsevier B.V., 2016)
Endoglucanases are the main cellulolytic enzymes secreted by the bacterium Xanthomonas campestris pv. campestris (Xcc). The major endoglucanase exported by this bacterium into an external milieu is an enzyme XccCel5A, which belongs to GH5 family subfamily 1 and is encoded by the gene engXCA. We purified XccCel5A using ammonium sulfate precipitation followed by size exclusion chromatography and identified it by zymogram analysis. Circular dichroism and fluorescence spectroscopy studies showed that XccCel5A is stable in a wide pH range and up to about 55 degrees C and denatures at the higher temperatures. The optimal conditions for enzyme activity were identified as T = 45 degrees C and pH = 7.0. Under the optimum conditions the catalytic efficiency (k(cat)/K-M) of the enzyme was determined as 5.16 x 10(4)s(-1) M-1 using carboxymethylcellulose (CMC) as a substrate. Our SAXS studies revealed extended tadpole-shape molecular assembly, typical for cellulases, and allowed to determine an overall shape of the enzyme and a relative position of the catalytic and cellulose binding domains. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Xanthomonas campestris; Endoglucanases; Hydrolysis; SAXS